Risk of being granted disability pension among incident cancer patients before and after a structural pension reform: A Danish population-based, matched cohort study - Pedersen, Pernille; Aagesen, Maria; Tang, Lars Hermann; Bruun, Niels Henrik; Zwisler, Ann-Dorthe; Stapelfeldt, Christina M. (Scandinavian Journal of Work, Environment & Health, 2020)
' ' OBJECTIVE ': 'This study aimed to examine the risk of being granted a disability pension (DP) among incident cancer patients up to five years after diagnosis compared to a match control group, before and after the structural reform of the Danish Disability Pension Act in 2013. ' ' METHODS ': 'All 20–60-year-old incident cancer-diagnosed individuals from 2000 to 2015 were identified in the Danish Cancer Registry. A control group, not previously diagnosed with cancer, was identified in Statistics Denmark matched by gender, age, education, and household income. Risk differences (RD) in cumulative incidence proportions of being granted a DP between cancer patients and controls were analyzed before and after the reform. ' ' RESULTS ': 'In total, 111 773 incident cancer patients and 506 904 controls were included in the study. Before reform 10 561 cancer patients and 11 231 controls were granted DP; and 2570 cancer patients and 2646 controls were granted DP after the reform. The adjusted RD of being granted DP was significantly higher for cancer patients versus controls at all time points before the reform. The RD increased the most during the first (RD 3.6, 95% CI 3.5–3.7) and second (RD 7.2, 95% CI 7.0–7.4) follow-up year and levelled off the remaining three years. After the reform, the adjusted RD were lower for all 1–5 follow-up years compared to before the reform (RD range 2.8–7.7, 95% CI 2.6–8.1). ' ' CONCLUSION ': 'The 2013 reform of the Disability Pension Act reduced the risk of cancer patients being granted DP. The impact on a personal level should be further explored.
Keywords: cancer; cohort study; Denmark; disability; disability pension; pension; pension reform; quality of life; return to work; vocational rehabilitation